2022
DOI: 10.2147/tcrm.s361936
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Predictive Nomogram with Age and Laboratory Findings for Severe COVID-19 in Hunan Province, China

Abstract: Purpose To identify more objectively predictive factors of severe outcome among patients hospitalized for coronavirus disease 2019 (COVID-19). Patients and Methods A retrospective cohort of 479 hospitalized patients diagnosed with COVID-19 in Hunan Province was selected. The prognostic effects of factors such as age and laboratory indicators were analyzed using the Kaplan–Meier method and Cox proportional hazards model. A prognostic nomogram model was established to pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 65 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…Previous studies [24][25][26] concluded that elderly patients were at increased risk to deteriorate during the course of a COVID-19 infection. A model created by age and laboratory findings showed that patients > 65 years of age had a substantially increased probability of developing a severe COVID-19 infection than patients < 65 years of age [27]. Earlier nomograms with clinical characteristics also demonstrated that age was a significant variable in severe cases [1,17].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [24][25][26] concluded that elderly patients were at increased risk to deteriorate during the course of a COVID-19 infection. A model created by age and laboratory findings showed that patients > 65 years of age had a substantially increased probability of developing a severe COVID-19 infection than patients < 65 years of age [27]. Earlier nomograms with clinical characteristics also demonstrated that age was a significant variable in severe cases [1,17].…”
Section: Discussionmentioning
confidence: 99%